IMPROVEMENT OF THE REGENERATOR USED IN CLEANING COTTON FROM IMPURITIES (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article presents the results of research work on the development of a new cotton regenerator for the extraction of cotton volatiles from waste cleaners. The main distinguishing features of the design and technological process of the new cotton regenerator for the extraction of cotton volatiles from waste cleaners are described.